Analysis of Waste Management with Fly Density Level in RT03 RW04, Kartoharjo Village, Nganjuk District, Nganjuk Regency - Ribut Hariati; Fidi Setyawan (Universitas STRADA Indonesia, 2020)
Background Behind : The high density of flies in RT03 RW04, Kartoharjo Village, Nganjuk District, Nganjuk Regency. Based on the initial survey, the results of fly density measurements were 16 flies from five surveyed houses . Objectives : This study aims to determine the effect of fly density levels on waste management . Methods : The research design in this study is observational Cross-sectional, namely to determine the effect of fly density levels on waste management. Where data concerning independent and dependent variables are collected at once at one time. Determination of Population Number of houses 70. Determination of samples with the formula n = N / 1 + Ne² = 70 / 1 + (70x0.05²) = 70 / 1 + (70x0.0025) = 70 / 1 + (0.175) = 70 / 1.175 = 59.57. Then 60 samples were obtained. The instrument used to measure waste management is filling out a questionnaire with observation while to measure fly density using the Fly Grill tool. The sampling technique uses Simple Random Sampling. The data is analyzed in the form of tables and Chi Square tests. Results : From this study, namely Good waste management as many as 30 (50%), poor waste management as many as 30 (50%). The density of flies obtained was low as many as 28 (46.67%), Medium as many as 10 (16.67%), High as many as 17 (28.33%), Very High as many as 5 (8.33%). Conclusion : Waste management affects the density of flies (significance 0.00 <0.05). Furthermore, suggestions related to the results of the study are the environment of RT03 RW04, Kartoharjo Village and the Health Office (Nganjuk Health Center) to plan activities in order to improve waste management so that it can reduce the level of fly density Copyright © 2018 Universitas Ahmad Dahlan .